ANALISIS PERKEMBANGAN SEKTOR KEUANGAN: SEBUAH PERSPEKTIF FINANCIAL DEEPENING DI INDONESIA TAHUN 1997-2021 - Husna, Talita Thea; Soebagiyo, Daryono (JPEKBM (Jurnal Pendidikan Ekonomi, Kewirausahaan, Bisnis dan Manajemen), 2023)
The financial sector plays an important role in the economic development of a country. A financial sector that grows in an orderly and systematic manner is able to promote economic activity. Meanwhile, a financial sector that is difficult to grow in an orderly and systematic manner can trigger the economy to encounter liquidity constraints to achieve better economic growth. This study aims to determine the effect of Real Interest Rates, Exchange Rates, and Inflation on Financial Deepening in Indonesia in 1997-2021. The data used is time series data for 1997-2021 using the Ordinary Least Square (OLS) approach. The results of the study show that the interest rate variable Real (IR) and Rupiah Exchange Rate (ER) variables have a significant influence on the Financial Deepening variable, while the Inflation variable (INF) does not have a significant effect on the Financial Deepening Variable.